2011
DOI: 10.4314/ejhs.v21i1.69047
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C viruses Infections and Their association with Human Immunodeficiency Virus: A cross-sectional study among blood donors in Ethiopia

Abstract: BackgroundSince the introduction of Highly Active Anti-Retroviral Therapy and the dramatic improvement in the prognosis of individuals with Human Immunodeficiency Virus, liver disease due to chronic viral hepatitis has become as important cause of morbidity and mortality in co-infected individuals. The objective of the study was to determine the Sero-prevalence of Hepatitis B Virus, Hepatitis C Virus and Human Immunodeficiency Virus and the association of the virus with Hepatitis B Virus and Hepatitis C Virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 21 publications
6
31
10
Order By: Relevance
“…However, the HBsAg prevalence in this group was a bit higher (8.4%) than the community based studies (8.0%), but in agreement with reports on blood donors of other African countries [70–72]. Nevertheless, in Ethiopia, studies in this group showed a marked variation even in the same locality with exceptionally highest [8, 14] or lowest [13, 15] prevalence rates over time. Apart from geographical location and study time differences, the discrepancies in this group in particular and other groups in general could be due to methodological drawbacks such as small sample size seen from southwest Ethiopia [14] and ill-defined study design from northwest Ethiopia [50].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the HBsAg prevalence in this group was a bit higher (8.4%) than the community based studies (8.0%), but in agreement with reports on blood donors of other African countries [70–72]. Nevertheless, in Ethiopia, studies in this group showed a marked variation even in the same locality with exceptionally highest [8, 14] or lowest [13, 15] prevalence rates over time. Apart from geographical location and study time differences, the discrepancies in this group in particular and other groups in general could be due to methodological drawbacks such as small sample size seen from southwest Ethiopia [14] and ill-defined study design from northwest Ethiopia [50].…”
Section: Discussionsupporting
confidence: 88%
“…2a). Moreover, the reports from the blood donors of the same localities like in Bahir Dar (25 vs. 4.11%) [8, 13], Jimma (24.2 vs. 2.1%) [14, 15] and Gondar (14.4 vs. 4.7%) [16, 17] showed marked epidemiological discrepancies over time (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the prevalence of HBV in this study was higher when compared to the 2.4% and 4.1% prevalence reported from Uganda and Rwanda respectively as well as 3.9% HBsAg prevalence in Addis Ababa [17] [24].…”
Section: Discussioncontrasting
confidence: 98%
“…They are virus hepatitis B virus , hepatitis C virus dan Human Immu-nodeficiency Virus (Yami et al 2011) [5,17].…”
Section: Introductionmentioning
confidence: 99%
“…More than 240 million people worldwide are chronically infected with the hepatitis B virus, between 500 up to 700,000 people die every year because of heart. More than 350,000 people die annually due to the disease hepatitis C [18,29]. According to the data of the Basic Health Research from the Ministry of health of Indonesia by 2013, the prevalence of hepatitis in Indonesia infected with virus hepatitis was 1.2%, two times higher than in 2007 [15].…”
Section: Introductionmentioning
confidence: 99%